2016
DOI: 10.1002/tox.22301
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol a induces steatosis in HepaRG cells using a model of perinatal exposure

Abstract: Human exposure to bisphenol A (BPA) could favor obesity and related metabolic disorders such as hepatic steatosis. Investigations in rodents have shown that these deleterious effects are observed not only when BPA is administered during the adult life but also with different protocols of perinatal exposure. Whether perinatal BPA exposure could pose a risk in human is currently unknown, and thus appropriate in vitro models could be important to tackle this major issue. Accordingly, we determined whether long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 84 publications
0
29
0
Order By: Relevance
“…First, wild-type (WT) and AhR-deficient HepaRG cells were characterized in nonsteatotic condition ( Figure 6 ). Compared to WT HepaRG cells, mut AhR HepaRG cells expressed very low levels of the AhR protein but presented normal (or subnormal) levels of CYP2E1, CYP3A4, albumin, and aldolase B ( Figure 6(a) ), which are specifically expressed in differentiated HepaRG cells [ 26 ]. Importantly, the mut AhR HepaRG cells were fully irresponsive to the dose-dependent effect of ITE on EROD activity ( Figure 6(b) ), thus indicating that the remaining low expression of AhR was unable to activate the expression of CYP1A1/2 and CYP1B1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, wild-type (WT) and AhR-deficient HepaRG cells were characterized in nonsteatotic condition ( Figure 6 ). Compared to WT HepaRG cells, mut AhR HepaRG cells expressed very low levels of the AhR protein but presented normal (or subnormal) levels of CYP2E1, CYP3A4, albumin, and aldolase B ( Figure 6(a) ), which are specifically expressed in differentiated HepaRG cells [ 26 ]. Importantly, the mut AhR HepaRG cells were fully irresponsive to the dose-dependent effect of ITE on EROD activity ( Figure 6(b) ), thus indicating that the remaining low expression of AhR was unable to activate the expression of CYP1A1/2 and CYP1B1.…”
Section: Resultsmentioning
confidence: 99%
“…A clonal selection was performed by seeding 1 cell/well in a 96-well plate. After growth and expansion, the cell clone of interest (henceforth referred to as mut AhR -HepaRG cells) was selected among about 60 different clones on four parameters: (1) cell morphology, (2) AhR mRNA and protein expression, (3) EROD activity after a 2-day treatment with the potent AhR activator ITE, and (4) mRNA and protein expression of aldolase B, albumin, CYP3A4, and CYP2E1, which are bona fide markers of hepatocellular differentiation [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, there was a significant correlation between the PGC1a mRNA expression and the phospho-AMPKa/total AMPK ratio in treated HepaRG cells. Despite these advantages, HepaRG cells present some limitations, as previously pointed out (Michaut et al, 2016;Bucher et al, 2017). For instance, this cell line derives from one female patient and thus does not allow identifying gender differences or genetic susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Undifferentiated and differentiated HepaRG cells have distinct gene expression profiles that tend to reflect the patterns seen in fetal and adult human liver, respectively. Genes that are primarily expressed in fetal hepatocytes, such as CYP3A7 and pyruvate kinase muscle isozyme, are more highly expressed in undifferentiated HepaRG cells, whereas genes that are predominantly expressed in adult hepatocytes, such as CYP3A4 and CYP2E1, are more highly expressed in differentiated HepaRG cells (Tsuji et al, 2014;Bucher et al, 2017). HepaRG cells are becoming established as a useful model for studying hepatocellular differentiation, xenobiotic metabolism and toxicity, and development of liver diseases (Sharanek et al, 2015;Nunn et al, 2016;Rodrigues et al, 2016;Sayyed et al, 2016;Xia et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies using HepaRG cells have used differentiated cells as a model to complement the use of primary cultured human hepatocytes (Josse et al, 2008; Lubberstedt et al, 2011; Gerets et al, 2012;Klein et al, 2015). However, few studies have evaluated the changes in xenobiotic-metabolizing enzyme expression that occur as HepaRG cells pass through the stages of the differentiation process (Aninat et al, 2006;Hart et al, 2010;Ceelen et al, 2011;Tsuji et al, 2014;Bucher et al, 2017), and no studies have determined expression of the individual SULTs. We found that SULT1B1, SULT1C2, SULT1C3, SULT1C4, and SULT1E1 mRNA levels were highest in confluent HepaRG cells, whereas SULT2A1 RNA levels increased throughout the differentiation process.…”
mentioning
confidence: 99%